IMPLEMENTASI KEBIJAKAN PENGURANGAN SAMPAH PLASTIK DI DINAS LINGKUNGAN HIDUP KOTA PALU - WANTI, ASMA; Tawil, Muzakir; F Labiro, Richard (JPS: Journal of Publicness Studies, 2024)
ASMAWANTI B 101 20 122, with title “Implementation of Policy Plastic Waste Reduction in The Palu City Environment Office”. Supervised by Muzakir Tawil as the supervisor with Richard F. Labiro as co-supervisor This study aims to determine the Implementation of Plastic Waste Reduction Policy at the Environmental Service of Palu City. The research method used is Descriptive Qualitative, the data collection techniques used are observation, in-depth informant interviews and documentation to collect the required data in the form of primary and secondary data. While the informants in this study amounted to 7 people, namely 4 people from the Palu City Environmental Service and 3 people from the Palu City community. The theory used in this research is the theory of George C. Edward III which has four indicators namely Communication, Resources, Disposition, and Bureaucratic Structure. Based on the results of the study, it shows that the Implementation of the Plastic Waste Reduction Policy at the Environmental Service of Palu City cannot be said to be running well. This can be seen from the indicators of the research results which include aspects of communication among the general public that are still lacking, it can be seen in the transmission indicators that the government has done, but socialization is only carried out in modern retail and also for the delivery of information and clarity about reducing plastic waste has not gone well. Human resources are not yet good, the budget for the operational funds of the plastic waste reduction program is not sufficient, as well as the facilities at TPS 3R and the waste transportation fleet are not yet adequate. The disposition or attitude of implementers is good because policy implementers have carried out their duties, it's just that there are still obstacles faced and good standard operating procedures (SOPs) for reducing plastic waste. As for suggestions for the implementation of plastic waste reduction policies at the Palu City Environmental Service to run well, it must improve communication, namely in the transmission or dissemination of information evenly to the public and need to increase facilities and infrastructure such as waste transportation fleets and completeness of TPS 3R facilities. And for the community it is suggested that there needs to be awareness of the environment to care about reducing plastic waste in Palu City.